2014
DOI: 10.1021/bm5012618
|View full text |Cite
|
Sign up to set email alerts
|

Acrylate-Tethering Drug Carrier: Covalently Linking Carrier to Biological Surface and Application in the Treatment of Helicobacter pylori Infection

Abstract: The development of carriers to sustain drugs at stomach surface is an attractive strategy to increase drug bioavailability locally and systematically. So far, the only reported carrier that can form a covalent bond with mucus, the thiolated carrier, relies on a reversible disulfide exchange reaction between thiols on the carrier and disulfide bridges on the mucus. Here we show the design and fabrication of a cellulose carrier with tethering acrylate groups (denoted here as clickable carrier) that, under a nont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…While some limitations still exist in thiol-click chemistries, ,, as previously mentioned, the disulfide bond is relatively stable in oxidizing and physiologic pH conditions. Disulfide cleavage-based compounds have been employed for chemosensing, in the development of prodrugs, hydrogels, and nanocarriers, and in material fabrication. , Thiol-click reaction with disulfides for site-specific protein–polymer conjugation has been reported previously, for instance, the generation of free thiols by reducing the cystine disulfide bridge in a peptide (salmon calcitonin), or protein (mucin), for subsequent polymer attachment. However, the concept of disulfide-based click reaction with synthetic polymers containing cyclic disulfide bonds has not been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…While some limitations still exist in thiol-click chemistries, ,, as previously mentioned, the disulfide bond is relatively stable in oxidizing and physiologic pH conditions. Disulfide cleavage-based compounds have been employed for chemosensing, in the development of prodrugs, hydrogels, and nanocarriers, and in material fabrication. , Thiol-click reaction with disulfides for site-specific protein–polymer conjugation has been reported previously, for instance, the generation of free thiols by reducing the cystine disulfide bridge in a peptide (salmon calcitonin), or protein (mucin), for subsequent polymer attachment. However, the concept of disulfide-based click reaction with synthetic polymers containing cyclic disulfide bonds has not been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, polyethylene oxide-acrylate (PEO-Acr) substituted ethyl cellulose has been synthesized to develop nanoparticles that may modulate the mucus microstructure [169]. The investigators hypothesized that the acrylate-terminated ethyl cellulose would react via thiol-ene click reaction with the thiols generated from the treatment of mucin with biocompatible reducing agents.…”
Section: Recent Developments In Targeting Oral Nanoparticles To Spmentioning
confidence: 99%
“…The investigators hypothesized that the acrylate-terminated ethyl cellulose would react via thiol-ene click reaction with the thiols generated from the treatment of mucin with biocompatible reducing agents. The investigators demonstrated that the treatment of mucin with tris (2-carboxyethyl) phosphine hydrochloride (TCEP) or vitamin C could generate free thiols that subsequently react with the PEO-Acr terminated ethyl cellulose [169]. Furthermore, ex vivo studies on porcine stomach showed that PEO-Acr terminated fluorescent ethyl cellulose nanoparticles could bind to the mucosal surface in the presence of reducing agent TCEP, and the extent of binding was greater than that of non-modified fluorescent ethyl cellulose nanoparticles.…”
Section: Recent Developments In Targeting Oral Nanoparticles To Spmentioning
confidence: 99%
See 1 more Smart Citation